Pigeons discriminate objects on the basis of abstract familiarity - Stephan, Claudia; Wilkinson, Anna; Huber, Ludwig (Animal Cognition, 2013)
Knowledge of previous encounters with conspecifics is thought to be beneficial as it allows fast and appropriate behavioral responses toward those animals. This level of categorization goes beyond perceptual similarity and requires the individual to refer to a more abstract common referent, namely familiarity. It has been shown that pigeons are able to form functional classes of conspecifics that are based on familiarity. To date, we do not know whether this ability is restricted to the social context (including heterospecifics) or if it can also be used to classify inanimate objects. Furthermore, the factors influencing the formation of this functional class are still unknown. Here, we show that pigeons (Columba livia) are able to use a categorical rule of familiarity to classify previously unseen photographs of objects from their living environment. Pigeons that lacked real-life experience with the objects were not able to do so. This suggests that perceptual features alone were not sufficient for class recognition. To investigate the impact of additional functional properties of the objects, familiar objects were further divided into two subcategories, namely those that were considered functionally relevant to the birds and those that were not. Although the majority of pigeons learned to categorize photographs of objects based on familiarity alone, our results also suggest an unlearned preference for “relevant” familiar objects. The results presented here suggest that pigeons are able to learn to extract the discriminative feature of abstract familiarity from pictures by referring to previous real-life experience but that additional functions of objects lead to a preference of these objects.<br
Keywords: Familiarity; Pigeon; Inanimate objects; Functional relevance; Picture-object recognition; Abstract categorization